The Work of the Sixth Committee of the United Nations General Assembly in 2016 and 2017 - Pronto, Arnold (South African Yearbook of International Law, 2020)
The following is a further instalment in a series reviewing the activities of the Sixth (legal) Committee of the General Assembly of the United Nations, focusing on the seventy-first (2016) and Seventy-second (2017) sessions. The review retains the three-tier structure of its predecessors, whereby the work of the Sixth Committee is broadly organised into three main types of activities: the substantive consideration of certain legal issues; the review of the annual work of expert legal bodies; and the discharge of certain oversight functions. A fourth category, namely the review of requests for observer status in the General Assembly, has also become a standard feature of the annual work of the committee.